2008
DOI: 10.1681/asn.2008010113
|View full text |Cite
|
Sign up to set email alerts
|

Gq-Dependent Signaling Upregulates COX2 in Glomerular Podocytes

Abstract: Accumulating evidence suggests that upregulation of cyclooxygenase 2 (COX2) in glomerular podocytes promotes podocyte injury. Because Gq signaling activates calcineurin and calcineurin-dependent mechanisms are known to mediate COX2 expression, this study investigated the role of Gq␣ in promoting COX2 expression in podocytes. A constitutively active Gq ␣ subunit tagged with the TAT HIV protein sequence was introduced into an immortalized podocyte cell line by protein transduction. This stimulated inositol trisp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
49
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(54 citation statements)
references
References 53 publications
4
49
1
Order By: Relevance
“…Similarly, Harris and coworkers 31 showed that puromycin aminonucleoside-induced apoptosis was attenuated in response to antagonism of the Gq-coupled TP receptor but not antagonism of the Gs-coupled EP4 receptor. The work of Spurney and colleagues 36 is consistent with these findings; they demonstrated that overexpression of a constitutively active Gq ␣ subunit stimulated calcineurin activity and was associated with podocyte apoptosis in vitro. The notion that Gq-but not Gs-coupled signaling promotes podocyte apoptosis is supported by a number of studies examining effects of the angiotensin II type 1 (AT1) receptor.…”
Section: Discussionsupporting
confidence: 58%
“…Similarly, Harris and coworkers 31 showed that puromycin aminonucleoside-induced apoptosis was attenuated in response to antagonism of the Gq-coupled TP receptor but not antagonism of the Gs-coupled EP4 receptor. The work of Spurney and colleagues 36 is consistent with these findings; they demonstrated that overexpression of a constitutively active Gq ␣ subunit stimulated calcineurin activity and was associated with podocyte apoptosis in vitro. The notion that Gq-but not Gs-coupled signaling promotes podocyte apoptosis is supported by a number of studies examining effects of the angiotensin II type 1 (AT1) receptor.…”
Section: Discussionsupporting
confidence: 58%
“…In the context of previous studies, 13 these findings suggest that a mechanistic pathway of increased expression of COX-2 in the injured glomerulus triggers local generation of PGE 2 with activation of the EP4 receptor in podocytes, causing exaggerated proteinuria and glomerular damage. This pathway may work in parallel with enhanced thromboxane production and TP receptor activation.…”
supporting
confidence: 67%
“…These data are also consistent with a more recent report from a different group. 13 Thus, it is probably safe to conclude that either deficient or excess podocyte-derived VEGF is bad for the filtration barrier. Both perturbations lead to proteinuria but by dichotomous pathobiological routes.…”
Section: Disclosuresmentioning
confidence: 99%
“…As previously reported, induction of GqQ>L does not cause glomerular injury (28), suggesting that a "second hit" may be required to induce podocyte injury, as has been suggested for Familial forms of focal segmental glomerulosclerosis (FSGS) have been linked to gain-of-function mutations in the gene encoding the transient receptor potential channel C6 (TRPC6). GPCRs coupled to Gq signaling activate TRPC6, suggesting that Gq-dependent TRPC6 activation underlies glomerular diseases.…”
Section: Introductionmentioning
confidence: 72%
“…To investigate the role of Gq signaling in the pathogenesis of glomerular diseases, we expressed a constitutively active Gq α subunit (Gq Q209L , herein referred to as GqQ>L) specifically in podocytes in a doxycycline-inducible (DOX-inducible) fashion (28). As previously reported, induction of GqQ>L does not cause glomerular injury (28), suggesting that a "second hit" may be required to induce podocyte injury, as has been suggested for Familial forms of focal segmental glomerulosclerosis (FSGS) have been linked to gain-of-function mutations in the gene encoding the transient receptor potential channel C6 (TRPC6).…”
Section: Introductionmentioning
confidence: 99%